Historical archaeology through a Western lens - Warner, Mark S.; Purser, Margaret Sermons (Historical archaeology of the American West., 2017)
"An exploration of Western historical archaeologists' role in American regionalism and a call for creating archaeologies of the West as an alternative to the isolated archaeologists working in the West"--Provided by publisher.